Intraosseous Lipoma Mimicking Periapical Lesion: A Rare Presentation - Abhishek Bannerjee; Snehashish Ghosh; Moumalini Das; Patrick Wang; Saranya Ramsridhar; Shankargouda Patil (Hindawi Limited, 2022)
Lipoma is one of the benign soft-tissue tumors in the adipose tissue. Oral lipomas comprise 1%-5% of benign oral tumors. They are slow-growing, soft, asymptomatic, solitary tumors. In this case report, a 45-year-old female patient having swelling on the upper right arch for 2 months has been reported. Clinically, the right upper second premolar and first molar were grossly carious, with diffuse swelling on the adjacent vestibule. A provisional diagnosis of the periapical abscess was rendered. Radiological evaluation and routine blood tests were performed. After the tissue was obtained, following teeth extraction and socket curettage, it was sent for histopathological evaluation, and findings suggested intraoral intraosseous lipoma. Clinically, they are asymptomatic, and therefore, if it was not curetted and histopathologic evaluation not done, and only thought to be just a swelling or a periapical abscess, proper treatment could not have been established. This paper will surely bring out the importance of histopathology in routine dentistry and the role of histopathological evaluation of periapical soft tissues.